2014
DOI: 10.1590/0103-6440201302250
|View full text |Cite
|
Sign up to set email alerts
|

Temporomandibular Disorders in a Sample Population of the Brazilian Northeast

Abstract: Temporomandibular disorder (TMD) is a common condition. This study is part of a research group and it investigated the prevalence of TMD and myofascial pain and its association with gender, age and socioeconomic class. The sample comprised 100 subjects, aged 15 to 70, users of the Family Health Units' services, in the city of Recife, PE, Brazil. The TMD degree was evaluated using the Research Diagnostic Criteria for TMD and socioeconomic class by the Economic Classification Criteria Brazil. Categorical variabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0
10

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 12 publications
(37 reference statements)
3
12
0
10
Order By: Relevance
“…According to the SQ-TMD survey results of a working population of 2203 subjects, the prevalence of the H-TMD was 16.4% [9]. It was reported that TMD were a significant public health problem affecting approximately 5% to 12% of the population [2], and the prevalence among those younger than 30 years was higher than in those older than 30 years [14, 15]. Our result was consistent with the results of these studies.…”
Section: Discussionsupporting
confidence: 90%
“…According to the SQ-TMD survey results of a working population of 2203 subjects, the prevalence of the H-TMD was 16.4% [9]. It was reported that TMD were a significant public health problem affecting approximately 5% to 12% of the population [2], and the prevalence among those younger than 30 years was higher than in those older than 30 years [14, 15]. Our result was consistent with the results of these studies.…”
Section: Discussionsupporting
confidence: 90%
“…Most of the patients with TMD are young adults aged between 20 and 40 years, and more commonly, females. [10] Early intervention can reduce the severity of disease. TMJ osteoarthritis represents a destructive process in which the bony surfaces of condyle and fossa become altered.…”
Section: Discussionmentioning
confidence: 99%
“…Apesar do número reduzido de sujeitos, o estudo se encontra em concordância com a literatura, uma vez que estudos mostram que a DTM tem maior prevalência no sexo feminino 9,11,17 . Pesquisas referem que este dado ocorre em decorrência das mulheres apresentarem maior busca a tratamentos em relação aos homens, ao maior nível de estrogê-nio, ao ciclo menstrual 2 e até pela maior ansiedade neste gênero 5 .…”
Section: Discussionunclassified
“…com a Academia Americana de Dor Orofacial, que aponta uma prevalência de DTM entre a segunda e quarta década de vida 2,11,18,19 . Com relação aos sintomas das DTMs investigados pelo questionário de anamnese desenvolvido pelos autores, estudos relatam que os mais frequentemente encontrados são a cefaleia 10,20 , os sintomas otológicos 11 , o ruído articular e limitação de amplitude de movimentos articulares 6,9,17 . Estes achados da literatura concordam com o quadro inicial de sintomas apresentado pelos pacientes do estudo.…”
Section: Discussionunclassified
See 1 more Smart Citation